Evolving Role of IT Program Managers in the Age of AI and Automation - Job , George (IPHO-Journal of Advance Research in Science And Engineering, 2025)
The integration of artificial intelligence and automation into enterprise IT ecosystems is fundamentally transforming the role of IT program managers, shifting their focus from administrative execution to strategic leadership. This paper examines how AI technologies are reshaping core program management functions, including planning and scheduling, risk management, resource allocation, and reporting, while simultaneously creating new demands for competencies beyond traditional project management skills. Through systematic analysis of recent literature, this article identifies that AI-driven tools enable program managers to transition from manual, labor-intensive processes to strategic decision-making roles that leverage predictive analytics, automated workflows, and real-time insights. The article reveals that successful adaptation to AI-augmented environments requires program managers to develop AI literacy, data fluency, ethical governance capabilities, and experimentation-driven mindsets while navigating the fundamental differences between traditional IT projects and iterative, data-dependent AI initiatives. The article further explores organizational adaptations necessary to support this evolution, including the transformation of Project Management Offices into Digital PMOs, the emergence of hybrid roles bridging technical and management functions, and the need for flexible career frameworks that accommodate diverse professional trajectories. By examining the intersection of AI capabilities and program management functions, this article contributes to understanding how traditional project management frameworks must evolve to remain relevant in increasingly automated landscapes, where the synthesis of human judgment and machine intelligence becomes the defining characteristic of successful program delivery.